Hydrogen cultivation through an integrated ranking cycle and proton exchange membrane with an evacuated tube collector powered by hybrid nanofluids - Sathish, T.; Giri, Jayant; Agbulut, Umit (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study integrates nanotechnology into renewable energy systems representing innovation in infrastructure development, crucial for sustainable industrial growth. The study addresses a critical need in renewable energy technology: enhancing hydrogen production rates through more efficient integration of solar thermal systems with Proton Exchange Membrane (PEM) electrolyzers and aligning the alignment with several Sustainable Development Goals 7, 9, and 13. By improving the efficiency of hydrogen production from renewable sources like solar energy, the study contributes to achieving sustainable energy solutions. The primary aim of the study is to investigate and demonstrate the efficacy of integrating an Evacuated Tube Solar Collector (ETSC) with a PEM electrolyzer, enhanced by nanofluids. Specifically, the study explores how nanotechnology can improve thermal performance and subsequently increase hydrogen production rates, particularly through Multi-walled carbon nanotubes (MWCNT), Magnesium oxide (MgO), and their hybrid. The nanoparticles such as MWCNT, and MgO were chosen at 0.1 % concentration and the hybrid was 0.05 % of each nanoparticle was chosen. The ranking cycle comprises the low, and high-pressure turbine for PEM electrolyzer. The result of the hybrid nanofluid in the ETSC circuit shows appreciable thermal performance than base fluid and standalone nanofluid. The peak outlet temperature by nanofluid is about 65.8 degrees C, 71.0 degrees C, and 78.5 degrees C by MWCNT, MgO, and hybrid nanofluid which is higher than Thermal oil respectively. The peak collector efficiency enhancement is about 80.5 % by integrating a hybrid nanofluid in an ETSC circuit. Similarly, the exergy efficiency was increased from 12.4 % to 36.8 by using a hybrid nanofluid in the ETSC circuit. The peak PEM electrolyzes energy, and exergy efficiency is about 44.4 %, and 10.5 % through the use of hybrid MWCNT/MgO nanofluid. The hydrogen production rate was increased from 6.8 % to 29.7 % when the hybrid nanofluid was used.
Keywords: Sustainable energy; Hydrogen production; Hybrid nanofluid; Clean fuel; Proton exchange membrane; PLATE SOLAR COLLECTOR; FLAT-PLATE; PERFORMANCE ANALYSIS; ENERGY; SYSTEM; Thermodynamics; Energy & Fuels